10.1146/annurev-nutr-072610-145121 (CrossRef Listing of Deleted DOIs, 2000)
Metabolite repair, or metabolite damage control, has emerged as a fundamental pillar of intermediary metabolism alongside catalysis and regulation. Enzyme promiscuity and spontaneous chemical reactions inevitably generate abnormal metabolites that can interfere with classical metabolic processes. Dedicated metabolite repair enzymes prevent or reverse such damage, thereby preserving metabolic integrity. Defects in these systems define a growing class of inborn errors of metabolism, several of which are now clinically recognized and, in some cases, treatable. We summarize recent advances in the discovery and characterization of metabolite damage and repair systems in the tricarboxylic acid cycle, glycolysis, and other pathways, highlighting examples with established or potential links to human disease. We outline strategies for identifying additional metabolite repair defects and discuss diagnostic challenges, therapeutic perspectives, and connections between metabolite repair and aging. Understanding metabolite repair exposes the mechanisms that safeguard metabolism and opens new paths toward molecular diagnosis and targeted therapy.